Efficacy of Actovegin in the treatment of the central and the peripheral nervous system - L. M. Boriskina (Нервно-мышечные болезни, 2015)
The stimulator of tissue regeneration Actovegin is used in many diseases associated with blood circulation. It’s given to patients with neurological, endocrinological, cardiac and even ophthalmic diseases. Its efficacy is observed in disorders of the brain with the metabolic and vascular nature. It improves the trophism of tissues with injuries, burns and ulcers of the different etiology. It prevents the development of adverse effects as a result of peripheral vascular disorders. Actovegin has received the active application in patients with the long-standing diabetes as a prevention and the treatment of complications, particularly the vascular dementia and the diabetic distal polyneuropathy. The basis for these diseases is the hypoxic nature of the tissue damage. It’s mechanisms direct to the reduction of the influence pathological factors and the recovery of the antioxidant activity of cells.